1975
DOI: 10.1016/0030-5073(75)90009-4
|View full text |Cite
|
Sign up to set email alerts
|

Job choice and post decision dissonance

Abstract: The job choice and post decision attitudes and behavior of 431 accounting students were studied. Data on the attractiveness of working for different firms was shown to be a good predictor of both the job application and the job choice behavior of the individuals. Data collected after the job choice decision was made showed that the chosen firms increased in attractiveness after choice and the rejected firms decreased. After one year of employment, the subjects rated all firms lower in attractiveness than they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(50 citation statements)
references
References 8 publications
1
49
0
Order By: Relevance
“…Part-time employment may have an effect, but this effect is ambiguous, with some studies finding a positive effect, some a negative one, and some none (Conway and Briner 2002). Time in job also affects job satisfaction: directly after finding a new job people are more satisfied with their job (the ''honeymoon effect''), but later they are less satisfied (the ''hangover effect'', e.g., Vroom and Deci 1971;Lawler et al 1975;Boswell et al 2009). Furthermore, having a mentor has been shown to contribute to job satisfaction, through an increase in self-confidence (e.g., Nick et al 2012).…”
Section: Job Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Part-time employment may have an effect, but this effect is ambiguous, with some studies finding a positive effect, some a negative one, and some none (Conway and Briner 2002). Time in job also affects job satisfaction: directly after finding a new job people are more satisfied with their job (the ''honeymoon effect''), but later they are less satisfied (the ''hangover effect'', e.g., Vroom and Deci 1971;Lawler et al 1975;Boswell et al 2009). Furthermore, having a mentor has been shown to contribute to job satisfaction, through an increase in self-confidence (e.g., Nick et al 2012).…”
Section: Job Satisfactionmentioning
confidence: 99%
“…A job at bachelor level or lower in turn negatively influences satisfaction. Also for terms of employment a longer time in job decreases satisfaction: the hangover effect (Vroom and Deci 1971;Lawler et al 1975;Boswell et al 2009). …”
Section: Satisfaction With Terms Of Employmentmentioning
confidence: 99%
“…A number of other studies have also concluded that measures of valence do not significantly contribute to predictions over and above the contributions of expectancies (e.g. Lawler et al, 1975;Schneider, 1976). The results of one study, however, have shown the predictive efficiency of the expectancy x valency model to be superior to using expectancies alone (Huber, Daneshgar & Ford, 1971).…”
Section: Resultsmentioning
confidence: 81%
“…A number of researchers have investigated the expectancy x valence model of job attraction (Vroom 1966;Vroom & Deci, 1971;Lawler, Kuleck, Rhode & Sorenson, 1975). These studies have consistently provided evidence of the utility of expectancy theory in predicting job attraction.…”
mentioning
confidence: 97%
“…Vroom's (1964) expectancy theory was widely adopted and considered the most influential one in studies about work-related criteria (Lawler III, Kuleck, Rhode, & Sorensen, 1975;Van Eerde & Thierry, 1996). A major contention of the theory is that a person's desired outcome (e.g., satisfaction with the potential employer) is a function of a combination of outcomes (i.e., factors leading toward satisfaction) weighted by their valence, which represents the importance of the outcomes (i.e., the factors) (Van Eerde & Thierry, 1996).…”
Section: Factors Driving Choice Of Employermentioning
confidence: 99%